FAKTOR - FAKTOR YANG MEMENGARUHI PENGGUNAAN JASA BANK MUAMALAT INDONESIA CABANG PEMBANTU BONE - Jumarni Jumarni (J-ESA (Jurnal Ekonomi Syariah), 2019)
The purpose of this study was to determine: (1) The effect of bank characteristics, services, facilities, promotions and products to use the services of Bank Muamalat Indonesia Branch Bone. (2) The most dominant factor to influence the decision of the services of Bank Muamalat branch Bone. The method that was used in this research is Multiple-linear Regression Analysis. The data used are primary data by giving questionnaires to selected respondents which contains a declaration of the independent variables consist of Bank Characteristics (X1), Services (X2), Facilities (X3), Promotion (X4) and Product (X5) while variable dependenya is the use of Bank Muamalat Services Capem Bone(Y). The results from this study shew that (1) The factors bank characteristics positive and significant impact on the decision to use the services of Bank Muamalat Indonesia Branch Bone (2) Service factor was positive and significant impact on the decision to use the services of Bank Muamalat Indonesia Branch Bone. (3) Factors facilities was positive and significant impact on the decision to use the services of Bank Muamalat Indonesia Branch Bone, (4) Factors promotion was positive and significant impact on the decision to use the services of Bank Muamalat Indonesia Branch Bone, (5) Product factor was positive and significant impact on the decision to use the services of Bank Muamalat Indonesia Branch Bone, (6) Product factor was the dominant factor affecting the use of the services of Bank Muamalat Indonesia Branch Bone, that was to 0322.